Fraudulent behavior in state financial management: A testing aspects of the fraud hexagon and individual morality - Pura, Rahman; Kartini, Kartini; Amiruddin, Amiruddin; Indrijawati, Aini (International Journal of Innovative Research and Scientific Studies, 2025)
The study aimed to investigate and analyze the influence of fraud hexagon aspects (stimulus, capability, collusion, opportunity, rationalization, and ego) and individual morality on fraudulent behavior among budget user officials in Regional Apparatus Organizations in Indonesia. This study used a quantitative survey approach, collecting data from 315 respondents using a structured questionnaire. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS).The findings reveal that aspects of the fraud hexagon, such as stimulus/pressure, capability, collusion, and rationalization affect on fraudulent behavior, while aspects of opportunity and ego do not affect on fraudulent behavior. Individual morality does not affect fraudulent behavior. This study has implications for the development of fraud theory by highlighting the importance of developing individual morality in relation to fraudulent behavior. Practical implications for the government in designing and implementing strategies for fraud prevention.